Diskursetnologi - Gerber, Sofi; Gunnarsson Payne, Jenny; Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2012)
How have ethnologists applied discourse theory? This text introduces the special issue of Kulturella Perspektiv called “Discourse ethnology”, in which nine Swedish ethnologists present their work with applying discourse theory. The introductory text briefly outlines the ontology of discourse theory and discusses articulatory practice as a way of thinking the move from ontology to application.